4th International Conference on Antenna Theory and Techniques (Cat. No.03EX699)
DOI: 10.1109/icatt.2003.1238839
|View full text |Cite
|
Sign up to set email alerts
|

Plasma antenna for magneto cumulative generator

Abstract: The physical model and experimental data of the plasma antenna designing are presented. The plasma antenna properties have been explored. The plasma antenna excitation tests have been done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The electron cyclotron radiation and pulse oscillation radiation are shown to be much weaker than the dipole oscillation radiation and surface wave radiation. The same investigations of a plasma dielectric antenna with other design was also made in [7]. It were shown that the main properties of such an antenna are: 1) plasma antenna action has many general with the dielectric antenna action; 2) plasma antenna is designed for pulse operation.…”
Section: Advanced Microwave and Millimeter Wave Technologies: Semiconmentioning
confidence: 98%
“…The electron cyclotron radiation and pulse oscillation radiation are shown to be much weaker than the dipole oscillation radiation and surface wave radiation. The same investigations of a plasma dielectric antenna with other design was also made in [7]. It were shown that the main properties of such an antenna are: 1) plasma antenna action has many general with the dielectric antenna action; 2) plasma antenna is designed for pulse operation.…”
Section: Advanced Microwave and Millimeter Wave Technologies: Semiconmentioning
confidence: 98%